The Importance of Polytechnics for Africa’s Development - Mohamedbhai, Goolam (International Higher Education, 2017)
Most African countries that were former British colonies replicated the British higher education system and created both universities and polytechnics. However, in order to increase their tertiary education enrolment, these countries are gradually upgrading their polytechnics to universities. This article argues that this is a wrong move as polytechnics are as important as universities for Africa’s development, and calls for a re-consideration of the polytechnics conversion policy.